Sistem Pendukung Keputusan Pemilihan Wilayah Prioritas Intervensi Kegiatan Keluarga Berencana Dengan Metode Simple Additive Weighting (Saw) Studi Kasus : Dinas Pengendalian Penduduk dan Keluarga Berencana Kota Binjai - Ahmad Fauzan Akbar; Magdalena Simanjuntak; Juliana Naftali Sitompul (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
Family Planning is an action that helps individuals or married couples to get certain objects that are run by the Office of Population Control and Family Planning (DPPKB) of Binjai City. Intervention is an activity that is carried out systematically and planned to change the condition of a person, group of people or society that leads to improvement or preventing the worsening of a situation. To select priority areas of intervention for family planning activities which include problems such as the selection process which takes a long time and allows for human error, a web-based decision support system is needed which is built using the Simple Additive Weighting (SAW) method. Keywords : Decision Support System (DSS), Simple Additive Weighting (SAW) Family Planning (KB), DPPKB Binjai City.